(untitled) (Altre Modernità, 2025)
Destination Italy in English translation and language over the years (1919-1959) (a cura di) Mirella Agorni (Università Ca’ Foscari Venezia) e Ilaria Parini (Università di Torino) Introduction by Mirella Agorni